THE ROLE OF SOCIAL MEDIA IN LIGHTING UP THE HISTORY OF UZBEKISTAN - Jabborova Nilufar Shavkatovna (Western European Studies, 2025)
This article discusses in detail the role of the National Television and Radio Company of Uzbekistan in covering the history of Uzbekistan, the programs, documentaries, and projects that currently provide our people with sound information about our history and past, teach lessons from the life and work of our ancestors, and also discuss the cultural heritage of our people. The author covers the content and essence of social media marketing in today's marketing system, its unique aspects, as well as the advantages and disadvantages of social media marketing, and the issues of development through social media marketing platforms
Keywords: Television; history; heritage; ancestors